Pengaruh Penambahan Jumlah Air terhadap Kekerasan, Kerapuhan dan Waktu Hancur Tablet Obat - Fitriyano, Gema; Prabowo, Aris; AB, Syamsudin; Kurniaty, Ika; Ismiyati, Ismiyati (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
The water content in the tablet is related to the compressibility of the tablet, because the water content formed acts as a binder that will fill the empty space between tablets. Excess water content in the tablet formulation can cause the tablet to become hydrophobic so that the tablet is difficult to wet during dissolution and travels in the body. Thus, the tablet will be more difficult to disintegrate in the stomach. The procedure for turning jackfruit seeds into flour are peeling, milling, and drying at a temperature of 105 oC. Following, water at 90 oC is mixed with jackfruit seed flour to make mocilago (mixture 1). fdc yellow and patent blue v dye into a beakerglass containing aquademin 95 oC then stir until completely uniform (mixture 2). Put mixture 1 into mixture 2 which has a temperature >80 oC. In the granulation stage, all ingredients are mixed with fine granulated sugar, magnesium hydroxide, dimethyl polysiloxane, some jackfruit seed flour and hydrotalcite to form mixture 3. Then add the binder solution Granule drying  and  drug printing processes follow. The characterization parameters of tablets produced in this research were tablet friability, tablet hardness and tablet disintegration time. Adding 193.2 mL of water to 25.6 grams of jackfruit seed powder was a variable that gives optimum effect on tablet hardness, friability, and disintegration time